Excitation of Saturnian ECH Waves Within Remote Plasma Injections: Cassini Observations. Issue 5 (7th March 2023) - Long, Minyi; Cao, Xing; Gu, Xudong; Ni, Binbin; Qu, Shaojie; Lou, Yuequn; Lai, Hairong; Ye, Shengyi; Wu, Siyuan; Zhao, Yiwen
Abstract: Based on Cassini observations, we report representative electrostatic electron cyclotron harmonic (ECH) wave events observed in Saturn's magnetosphere within remote plasma injections. Unlike local injections, remote injections are "older" injection events that have evolved to form a dispersed signature in particle energy spectrum. We show that Saturnian ECH waves within remote injections present a strong fundamental band and much weaker high harmonic bands. By calculating the linear wave growth rates based on the measured electron velocity distributions, we indicate that Saturnian ECH waves can be excited by the loss cone distribution of remotely injected, hot electrons of ∼100 eV to several keV. We find that ECH waves tend to intensify with increased fluxes of injected hot electrons but weakening with increased evolution time of the flux tubes, which is consistent with the results of wave growth rates and improves the current understanding of the generation of ECH waves at Saturn. Plain Language Summary: Saturn possesses a huge magnetosphere formed by the interaction between the solar wind flows and the internal magnetic field. Electrostatic electron cyclotron harmonic (ECH) waves are electrostatic emissions frequently observed in Saturn's magnetosphere, which occur near the half‐integral harmonics of electron cyclotron frequency ( f ce ), that is, ( n + 1/2) f ce . ECH waves are closely related to the injection events driven by the centrifugal force. Due to the gradient and curvature drift, the injected hot electrons produce dispersion signatures on the energy‐time spectrogram, which is a typical characteristic in the remote injections. In this work, we report typical ECH wave events in the remote injections and investigate the wave generation mechanism. Our results show that the excitation of ECH waves in the remote injections is caused by loss cone instability. The wave growth is dominated by injected hot electrons (∼100 eV–several keV). In addition, we find that ECH wave amplitudes increase as the hot electron fluxes increase and decrease with increasing ages of the injection events. Our results help us to deeply understand the generation of ECH waves in the Saturn's magnetosphere. Key Points: The loss cone instability of electrons excites the Saturnian electron cyclotron harmonic (ECH) waves within remote plasma injections The free energy for Saturnian ECH wave growth is mainly provided by remotely injected, hot electrons at energies of ∼100 eV to several keV Saturnian ECH waves intensify with increased fluxes of injected hot electrons but weakening with increased evolution time of the flux tubes